2017
DOI: 10.1371/journal.pone.0175365
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the associations among Helicobacter pylori infection, adiponectin, leptin, and 10-year fracture risk using the fracture risk assessment tool: A cross-sectional community-based study

Abstract: Helicobacter pylori (H. pylori) infection may induce inflammatory cytokines or adipokines that influence bone turnover and bone fracture risk. This study aimed to evaluate the association among H. pylori infection, adipokines, and 10-year fracture risk using the Fracture Risk Assessment Tool scale. From August 2013 to February 2016, a community-based cohort was surveyed by Keelung Chang-Gung Memorial Hospital. Subjects were included if they were older than 40 years and not pregnant. All participants underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…These factors can lead to several cardiovascular disorders and diabetes mellitus. It is a common condition affecting geriatric population (Kapil et al, ; Kapil et al, ), also leading to frailty (Lopez‐Garcia et al, ), sarcopenia (Chang et al, ), increasing the risk of fracture (Chen, Chen, Hsieh, Kuo, & Chien, ), osteoporosis (Cui et al, ), and affecting cognitive and functional abilities in this group of population (Viscogliosi, Donfrancesco, Palmieri, & Giampaoli, ). Yang and Xuan () demonstrated that H. pylori infection is associated with the increased risk of metabolic syndrome in Chinese population with the odds ratio of 5.427.…”
Section: Metabolic Syndromementioning
confidence: 99%
“…These factors can lead to several cardiovascular disorders and diabetes mellitus. It is a common condition affecting geriatric population (Kapil et al, ; Kapil et al, ), also leading to frailty (Lopez‐Garcia et al, ), sarcopenia (Chang et al, ), increasing the risk of fracture (Chen, Chen, Hsieh, Kuo, & Chien, ), osteoporosis (Cui et al, ), and affecting cognitive and functional abilities in this group of population (Viscogliosi, Donfrancesco, Palmieri, & Giampaoli, ). Yang and Xuan () demonstrated that H. pylori infection is associated with the increased risk of metabolic syndrome in Chinese population with the odds ratio of 5.427.…”
Section: Metabolic Syndromementioning
confidence: 99%
“…IL-1 and TNF- α trigger bone resorption [ 9 ]. In addition, osteoporosis is a condition with progressively decreasing BMD and increased bone fragility, with increased risk of bone fractures [ 10 ]. Metabolic syndrome and osteoporosis have become worldwide public health issue, especially in elderly subjects, with huge clinical and economic burdens.…”
Section: Introductionmentioning
confidence: 99%
“…Another mechanism postulated is that impaired gastric acidification (gastric mucosal atrophy and hypo-, and achlorhydria) related to H. pylori infection might induce malabsorption of calcium and alter bone architecture (9,(13)(14)(15)(16)(17)(18) . Asaoka et al (8) reported that endoscopic gastric mucosal atrophy tended to correlate with osteoporosis and suggested that the decrease of dissolution of calcium salts caused by the decrease in gastric acid secretion in atrophic gastritis may also result in the malabsorption of calcium.…”
Section: Discussionmentioning
confidence: 99%
“…There is also reduced bone mass in osteopenia, but without involvement of microarchitecture (2,6) . While several studies reported an association between H. pylori infection and osteoporosis (8,19,20) , some of them suggested that H. pylori infection would not to be a risk factor for decreased BMD (10,18) . There are studies determining immune response and cytokines in children with gastritis (12) , but the studies evaluating association between H.pylori infection and osteoporosis in children are limited (10) .…”
Section: Discussionmentioning
confidence: 99%